Hausdorff operators on homogeneous spaces of locally compact groups - Mirotin, Adolf R. (Journal of the Belarusian State University. Mathematics and Informatics, 2020)
Hausdorff operators on the real line and multidimensional Euclidean spaces originated from some classical summation methods. Now it is an active research area. Hausdorff operators on general groups were defined and studied by the author since 2019. The purpose of this paper is to define and study Hausdorff operators on Lebesgue and real Hardy spaces over homogeneous spaces of locally compact groups. We introduce in particular an atomic Hardy space over homogeneous spaces of locally compact groups and obtain conditions for boundedness of Hausdorff operators on such spaces. Several corollaries are considered and unsolved problems are formulated.
Keywords: Hausdorff operator; locally compact group; homogeneous space; atomic Hardy space; Lebesgue space; bounded operator